ND CONCENTRATION AND ISOTOPIC COMPOSITION DISTRIBUTIONS IN SURFACE WATERS OF NORTHWEST PACIFIC AND ITS ADJACENT SEAS - Amakawa H.; Alibo D.S.; Nozaki Y. (My University, 2004)
Nd isotopic composition and concentration distributions were determined in surface waters of the Northwest Pacific Ocean and its adjacent seas, i.e., the Okhotsk and Japan Seas. The Okhotsk and Japan Seas samples showed higher Nd concentrations (19∼31 pmol/kg) than the Northwest Pacific Ocean samples, suggesting a large amount of Nd input from the land areas surrounding the Okhotsk and Japan Seas. Although the Nd isotopic composition data were limited for those regions, each oceanic area showed a distinctive value. The lone sample from the Okhotsk Sea had radiogenic Nd (eNd = −3.6) that was comparable to samples from the Pacific Ocean, indicating a large amount of radiogenic Nd supply from the Kuril Islands. On the other hand, the Japan Sea samples had the most highly unradiogenic Nd (eNd = −8.9∼−7.2). The southernmost sample had the most negative value, due to the influence of the Tsushima Warm Current (TWC) having a low eNd value. The latitudinal distributions of Nd isotopic composition and concentration in the surface waters of the Northwest Pacific Ocean showed marked variations. Nd concentration was low at low latitudes (3∼8 pmol/kg) and was increased with increasing latitude (16∼20 pmol/kg). On the other hand, Nd isotopic composition showed a mid-latitude minimum (eNd = ∼−6) and high eNd values at low and high latitudes (eNd = −2∼−1). The distribution of the eNd values seemed to be controlled by three currents: Kuroshio Extension, Oyashio Current and North Equatorial Current (NEC). The Kuroshio Extension, which showed a low eNd value, seemed to play an important role in transporting continentally derived Nd to the central Pacific. The Oyashio Current and NEC are supplied with large amounts of radiogenic Nd from the Kuril and Aleutian Islands, and the Hawaiian Islands, respectively. Based on the Nd isotopic composition and concentration distributions, we calculated the radiogenic Nd flux to the Pacific Ocean surface waters and estimated the Nd residence time. Our calculation suggested that the radiogenic Nd flux required to account for the Nd isotopic composition is higher than 70% of the unradiogenic Nd flux including Nd remobilization from coastal and shelf sediments and atmospheric input. It was also revealed that a large Nd remobilization flux is necessary to attain a global Nd residence time of ∼400 y as estimated in previous studies.
Keywords: Nd isotopic composition; Nd concentration; surface water; North west Pacific Ocean; current